2022
DOI: 10.18805/ag.r-2545
|View full text |Cite
|
Sign up to set email alerts
|

Current Scenario of Crop Improvement of Finger Millet [Eleusine coracana (L.)] in India: A Review

Abstract: Finger millet [Eleusine coracana (L.) Gaertn.] is an ancient and important millet crop of India. The crop is predominantly grown as rainfed crop in the peninsular Indian states. The crop has shown numerous advantages over major cereals in terms of stress adaptation, nutritional quality and health benefits. Finger millet is highly self pollinated crop. Hybridization in finger millet is difficult due to small cleistogamous florets. Presently hot-water treatment followed by contact method of crossing is widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Additionally, the AICRP released the semi-dwarf, non-lodging cultivar GPU-67, suitable for wider adoption. Notably, around 45% of finger millet cultivars released in India, totaling about 145 varieties, from which about 45% have been developed through hybridization and selection (https://www.seednet.gov.in/; Nagaraja et al 2022).…”
Section: Early Efforts and Progress In Finger Millet Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the AICRP released the semi-dwarf, non-lodging cultivar GPU-67, suitable for wider adoption. Notably, around 45% of finger millet cultivars released in India, totaling about 145 varieties, from which about 45% have been developed through hybridization and selection (https://www.seednet.gov.in/; Nagaraja et al 2022).…”
Section: Early Efforts and Progress In Finger Millet Breedingmentioning
confidence: 99%
“…Resistance was found in eight cultivars viz., KOPN 21, RPS 594, RPS 531, KOPN 8, RPS 745, RBK 155, RPS 630 and KOPN 22 (Jain et al 2018). Nagaraja et al (2022) reported that about 40 varieties of kodo millets have been released in India.…”
Section: Kodo Millet (Kodo) Paspalum Scrobiculatum L 2n=4x=40mentioning
confidence: 99%
“…The increased humidity ensures the emergence of anthers from the florets without dispersing pollen in the polythene bag. These pollens are collected and dusted on the emasculated female panicle by tapping ( Nagaraja et al., 2022 ).…”
Section: Finger Milletmentioning
confidence: 99%
“…"High in dietary fiber: Finger millet is a good source of dietary fiber, which aids in digestion, promotes satiety, and helps maintain healthy blood sugar levels) [3][4][5][6]. Finger millet is naturally gluten-free, making it a suitable alternative grain for individuals with gluten intolerance or celiac disease" [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%